2015 15th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing 2015
DOI: 10.1109/ccgrid.2015.73
|View full text |Cite
|
Sign up to set email alerts
|

A Software Workbench for Interactive, Time Critical and Highly Self-Adaptive Cloud Applications (SWITCH)

Abstract: Time critical applications have very high requirements on network and computing services, in particular on well-tuned software architecture with sophisticated optimisation on data communication. Their development is often customised to dedicated infrastructure, and system performance is difficult to maintain when infrastructure changes. This fatal weakness in existing architecture and software tools causes very high development costs, and makes it difficult to fully utilise the virtualised, programmable and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
2

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…A major goal in the development of the SWITCH Interactive Development Environment (SIDE) [36], is to assure that the Quality of Service requirements are taken from the end-user early in the software design and engineering process. Once these requirements are semantically annotated and stored, they can be used later on during the use of the application to decide on which Cloud provider to deploy the application.…”
Section: Resultsmentioning
confidence: 99%
“…A major goal in the development of the SWITCH Interactive Development Environment (SIDE) [36], is to assure that the Quality of Service requirements are taken from the end-user early in the software design and engineering process. Once these requirements are semantically annotated and stored, they can be used later on during the use of the application to decide on which Cloud provider to deploy the application.…”
Section: Resultsmentioning
confidence: 99%
“…The Dynamic Real-time Infrastructure Planner (DRIP) is a system developed in the SWITCH project for the planning, validation and provisioning of the virtual infrastructure to support migrating applications onto clouds. The entire SWITCH) [12] workbench also includes other two subsystems: SIDE (SWITCH Interactive Development Environment). It is responsible for composing and describing applications; ASAP (Autonomous System Adaptation Platform).…”
Section: The Architecture and Techniques Of Cloudsstorm Frameworkmentioning
confidence: 99%
“…Based on edge and fog computing definitions [34], exiting technology reviews [35,36], the identified technical requirements of the potential applications, and experience gained in the course of advanced cloud computing and software engineering projects, such as mOSAIC [37], SWITCH [38] and ENTICE [39], an adequate conceptual approach for edge computing in construction is prepared. It defines the main necessary services that can be used to obtain high QoS.…”
Section: Methodsologymentioning
confidence: 99%